MOTIVATION IN LEARNING INDONESIAN AS A FOREIGN LANGUAGE FOR KOREAN STUDENTS - Defina, Defina; Sundari, Hanna (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2016)
Indonesia is now promoting the internationalization of Indonesian through Indonesian Language Program for Foreign Speakers (BIPA). Nowadays, many courses and university institutes both domestically and abroad open Indonesian program. It is actually caused by the increasing rate of Indonesian learners and one of them is people from South Korean. In this connection, the purpose of this paper is to identify the motivation they follow BIPA program. The method used was a survey with data collection through a questionnaire by adapting Attitude Motivation Test Battery (AMTB). Research conducted at the Language Center Foundation Hana (Hana Language Center), Jakarta. The respondents were 7 people. The theory used is the theory of integrative orientation and instrumental orientation proposed by Gardner. As a result, all learnersâ integrative orientations are wanted to communicate with the people of Indonesia, while the instrumental orientation is they all learn Indonesian as assigned in Indonesia. In conclusion, the orientations of integrative and instrumental orientation are in them all.